Coffee and Community : Maya Farmers and Fair-Trade Markets - Lyon, Sarah (Book collections on Project MUSE., 2011)
We are told that simply by sipping our morning cup of organic, fair-trade coffee we are encouraging environmentally friendly agricultural methods, community development, fair prices, and shortened commodity chains. But what is the reality for producers, intermediaries, and consumers? This ethnographic analysis of fair-trade coffee analyzes the collective action and combined efforts of fair-trade network participants to construct a new economic reality.